A novel hantavirus associated with an outbreak of fatal respiratory disease in the southwestern United States: evolutionary relationships to known hantaviruses. - Hjelle, B (1994)
Four Corners hantavirus (FCV) is the tentative name of the suspected etiologic agent of the newly identified hantavirus-associated respiratory distress syndrome (HARDS). The identification in HARDS patients of serum immunoglobulin M and immunoglobulin G antibodies that cross-reacted with Hantaan, Seoul, and Puumala virus antigens first suggested that FCV is a hantavirus. Limited nucleotide sequence data from the FCV glycoprotein-2 (G2) confirmed that FCV is a hantavirus and showed that it is most closely related to Prospect Hill and Puumala viruses. We have molecularly cloned approximately 95% of the sequences of the M and S segments of the FCV genome encoding the envelope glycoproteins and nucleocapsid protein N from the lungs of a patient with HARDS. The nucleotide sequence has been determined for 2,632 bases. The nucleotide sequence data show that FCV is a new member of the Puumala virus and Prospect Hill virus division of the hantavirus genus. Phylogenetic tree analyses indicate that the M and S segments have evolved in parallel. Therefore, the novel pathogenic activity of FCV is not likely to be the result of recent reassortment of segments from less pathogenic viruses.